Assessing Heritage Resources in St. Croix Post‐Hurricanes Irma and Maria. Issue 2 (24th September 2018) - Dunnavant, Justin P.; Flewellen, Ayana Omilade; Jones, Alexandra; Odewale, Alicia; White, William
Abstract: In the summer of 2017, we, as members of the Society of Black Archaeologists (SBA), initiated a sustainable archaeological project on the island of St. Croix in collaboration with several local and international partners. Only a few months later, Hurricanes Irma and Maria devastated much of the US Virgin Islands causing substantial loss in life and property, widespread displacement, damage to infrastructure, and negative impacts to important historical landscapes and heritage resources. This article outlines the effects of hurricane damage on African diaspora heritage sites in St. Croix and our response as Black archaeologists committed to community empowerment. Learning from the recent events, we offer recommendations for standardized methods of site documentation that can be adopted by archaeologists and heritage professionals working in the circum‐Caribbean to better assess site damage and develop protective conservation techniques before major catastrophic events.